The mechanism of ginger and its processed products in the treatment of estradiol valerate coupled with oxytocin-induced dysmenorrhea in mice via regulating the TRP ion channel-mediated ERK1/2/NF-κB signaling pathway. Issue 21 (12th October 2022) - Liu, Xiaoqin; Meng, Xianglong; Su, Xiaojuan; Ren, Kele; Ning, Chenxu; Qi, Xiaoming; Zhang, Shuosheng
Abstract : Mechanism of Ginger and its processed products in the treatment of estradiol valerate coupled with oxytocin-induced dysmenorrhea in mice via regulating the TRP ion channel-mediated ERK1/2 /NF-κB signaling pathway. Abstract : Ginger (Rhizoma zingiberis, RZ) has been used as a food, spice, supplement, flavoring agent, and as an edible herbal medicine. It is characterized by its pungency and aroma, and is rich in nutrients with remarkable pharmacological effects. It is used in traditional medicine clinics to treat diseases and symptoms, such as colds, headache, and primary dysmenorrhea (PD). In China, a variety of processed products of RZ are used as herbal medicines, such as baked ginger (BG) or ginger charcoal (GC) to treat different diseases and symptoms. However, the molecular mechanism of the therapeutic effect of RZ and its processed products (RZPPs, including BG or GC) against PD has not been well characterized. Moreover, whether the transient receptor potential (TRP) ion channels are involved in this process is not clear. In the present study, UHPLC-Q-TOF MS was adopted to analyse the differential quality markers (DQMs) between RZ and RZPPs. In addition, differential metabolomics (DMs) was acquired between RZ- and RZPPs-treated estradiol valerate coupled with an oxytocin-induced PD mouse uterus using untargeted metabolomics (UM). A correlation analysis between DQMs and DMs was also conducted. Benzenoids, lipids, and lipid-like molecules were the main DQMs between RZ and RZPPs. RZ and RZPPs were found to improve the pathological status of the uterus of a PD mouse, with significantly decreased serum levels of E2, PGF2α, TXB2 and remarkably increased levels of PROG and 6-keto-PGF1α . Moreover, RZ and RZPPs alleviated PD in mice via regulating the TRP ion channel-mediated ERK1/2 /NF-κB signaling pathway. Our results indicate that the therapeutic effect of RZ and RZPPs against PD may be mediated by regulating the TRP ion channel-mediated ERK1/2 /NF-κB signaling pathway, and provide a reference for the development of new dietary supplements or medicines.